Cigarette butts: more than waste, a toxic cellulose acetate residue - Jose Manuel Espinoza González (2025)
Cigarette butts are a common urban waste with a serious environmental impact due to their toxicity and slow breakdown. This essay reviews collection and recycling strategies, including clean-up campaigns, specialized bins, and chemical and physical processing for reusable materials. Their application in construction and biofuels is explored, along with the need for public policies and cross-sector cooperation. The proper use of cigarette butts reduces pollution and supports sustainable urban waste practices.